Realization of broadband and independent polarization metamaterial perfect absorber based on the third-order resonance - Hien, Nguyen Thi; Duyen, Phan Thi; Khuyen, Bui Xuan; Tung, Bui Son; Ca, Nguyen Xuan; Ha, Pham Thi Thu; Lam, Vu Dinh (Vietnam Journal of Science and Technology, 2020)
In this report, we studied numerically and experimentally the electromagnetic properties of perfect MAs using ring-shaped structures at microwave frequencies. By creating a magnetic resonance, the ring structure confines electromagnetic energy at the first- and third-order resonances. And then, we leveraged the super-cell structures, which consist of different rings in one unit cell to obtain broadband absorption. The results showed that the absorption band of MA is broaden from 1.3 to 2.17 GHz when the number of rings in the unit cell increases from four to nine-rings